2021
DOI: 10.3389/fnhum.2021.769619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synergism of Mindfulness Practice Associated With Transcranial Direct-Current Stimulation in Chronic Migraine: Pilot, Randomized, Controlled, Double-Blind Clinical Trial

Abstract: Chronic migraine is a difficult disease to diagnose, and its pathophysiology remains undefined. Its symptoms affect the quality of life and daily living tasks of the affected person, leading to momentary disability. This is a pilot, randomized, controlled, double-blind clinical trial study with female patients between 18 and 65 years old with chronic migraine. The patients underwent twelve mindfulness sessions paired with anodal transcranial direct-current stimulation (tDCS) over the left dorsolateral prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, the role of combined therapy on the overall improvements is not as clear across the remaining studies. Pimenta et al (2021) had a larger effect size for the group with active tDCS and MM despite including additional MM training. Robinson et al (2019) found significant results at a specific location with LKM, regardless of tDCS intensity, which could be explained by the lack of LKM and tDCS sessions.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the role of combined therapy on the overall improvements is not as clear across the remaining studies. Pimenta et al (2021) had a larger effect size for the group with active tDCS and MM despite including additional MM training. Robinson et al (2019) found significant results at a specific location with LKM, regardless of tDCS intensity, which could be explained by the lack of LKM and tDCS sessions.…”
Section: Discussionmentioning
confidence: 90%
“…The published studies included 664 participants, after correcting for secondary analyses publications using the same participants, comprising of 56.93% females and 43.07% males ( Table 1 ). Seven out of the 20 studies were conducted in healthy individuals ( Badran et al, 2017 ; Clarke et al, 2020 ; Danilewitz et al, 2021 ; Hunter et al, 2018 ; Nishida et al, 2021 ; Robinson et al, 2019 ; Sefat et al, 2022 ), while the remaining studies tested the combination of tDCS and meditation in patient groups diagnosed with conditions such as chronic pain ( Ahn et al, 2019; Pimenta et al, 2021 ; Pollonini et al, 2020 ; Ramasawmy et al, 2022 ), psychological disorders ( Alizadehgoradel et al, 2021 ; Brooks et al, 2021 ; Brown et al, 2020 ; Gibson et al, 2022 ; Hung, 2019 ; Monnart et al, 2019 ; Witkiewitz et al, 2019 ), mild cognitive impairment ( Liao et al, 2021 ), and movement disorders ( Park et al, 2021 ). All the ongoing studies test the combined intervention in diseased populations ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown, for the first time ever, the therapeutic effect of mindfulness practices associated with left dorsolateral prefrontal cortex anodal tDCS in improving the level of full attention and analgesic benefits in this patient population [75,76].…”
Section: New Treatment Optionsmentioning
confidence: 98%